MgB(2) Coils for MRI Applications - Yao, Weijun (IEEE Trans Appl Supercond, 2010)
In this paper, we report our progress in the development of a low cost, liquid-helium-free MgB(2) superconducting MRI magnet. Several technical issues related to the construction of such a magnet to operate in persistent current mode are discussed, namely, the performance consistency of long length MgB(2) conductors, the fabrication of superconducting joints and persistent current switches. Quench detection and protection of such magnets operated in solid nitrogen environment are also discussed.